1973
DOI: 10.1136/gut.14.9.683
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal permeability in animals and man

Abstract: SUMMARY The permeability ofthe human small intestine has been studied by measuring the clearance from the plasma into the intestinal lumen of substances with molecular weights ranging from 60 to 80 000. A direct relationship has been demonstrated between intestinal loss and plasma concentration and an inverse one between clearance and molecular size.The permeability of the rabbit small intestine has been studied at various levels by measuring the blood-to-lumen clearance of substances of different molecular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Parenteral injections of radiolabeled polyvinylpyrrolidone in humans demonstrated that the permeability cut-off of the human small intestine is MW of 80 000 Da. 24,25 The GI permeability "cut-off" MW was also confirmed using polyethylene glycol (PEG) 26,27 and, even for patients with irritable bowel syndrome, it is below 80 000 Da 28,29 and therefore an order of magnitude below the MW of PTFE which is in the million Das.…”
Section: Review Of Biological Safety Of Ptfementioning
confidence: 95%
“…Parenteral injections of radiolabeled polyvinylpyrrolidone in humans demonstrated that the permeability cut-off of the human small intestine is MW of 80 000 Da. 24,25 The GI permeability "cut-off" MW was also confirmed using polyethylene glycol (PEG) 26,27 and, even for patients with irritable bowel syndrome, it is below 80 000 Da 28,29 and therefore an order of magnitude below the MW of PTFE which is in the million Das.…”
Section: Review Of Biological Safety Of Ptfementioning
confidence: 95%
“…In fact, the jejunum is reported to have the highest perme-stage renal disease. Recognizing that high rates of perfusion provide relatively limited advantages in terms ability to creatinine of any gut segment [23,24,25]. It has been suggested that up to 66% of creatinine pro-of clearing solutes, we have recently described a continent in situ jejunal reservoir for dialysis [1].…”
Section: Effects Of Osmolality Of Perfusion Solution On Net Fluxmentioning
confidence: 99%
“…In addition, the presystemic disposition of the drug was also calculated by measuring the concentration of sildenafil appearing in the plasma during the intestinal perfusion experiment. The rabbit was selected in this study as the model animal because the rabbit GIT physiology is similar to that of the human [10][11][12]. …”
Section: Introductionmentioning
confidence: 99%